An Analysis of the Effectiveness of the Legal and Policy Framework in Promoting Talent Development in the Sports Industry of Uganda: A Case Study of Athletic Sports in the National High Altitude Training Center Teryet, Kapchorwa - Isaac Kwemboi (Uganda Christian University, 2025)
The study has been carried out using secondary source review of various statutes, articles, policies and journals about the topic under analysis. The study is aimed at analyzing the effectiveness of the legal and policy framework in promoting Talent Development for the success of elite sports. It is specifically aimed at; identifying and explaining in brief the legal and policy framework that govern talent development in sports in so far as it constitutes a national sport1 and an “economic activity” and lastly to recommend legal and Policy reforms for the sporting success.